2022
DOI: 10.1021/jacs.2c00476
|View full text |Cite
|
Sign up to set email alerts
|

Bis-periazulene (Cyclohepta[def]fluorene) as a Nonalternant Isomer of Pyrene: Synthesis and Characterization of Its Triaryl Derivatives

Abstract: Bis-periazulene (cyclohepta[def ]fluorene), which is an unknown pyrene isomer, was synthesized as kinetically protected forms. Its triaryl derivatives 1c−e exhibited the superimposed electronic structures of peripheral, polarized, and open-shell π-conjugated systems. In contrast to previous theoretical predictions, bis-periazulene derivatives were in the singlet ground state. Changing an aryl group controlled the energy gap between the lowest singlet−triplet states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 70 publications
3
33
0
Order By: Relevance
“…Very recently, other attractive systems have also been reported in which both neutral and cationic states were successfully isolated by applying the strategies described here. [128][129][130][131] The redox chemistry of pure hydrocarbons is expanding rapidly, and these examples will be covered in another review. Furthermore, although excluded from this review, the development of pure hydrocarbon-based response systems based on different approaches from electrochemical stimulation is also being actively pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, other attractive systems have also been reported in which both neutral and cationic states were successfully isolated by applying the strategies described here. [128][129][130][131] The redox chemistry of pure hydrocarbons is expanding rapidly, and these examples will be covered in another review. Furthermore, although excluded from this review, the development of pure hydrocarbon-based response systems based on different approaches from electrochemical stimulation is also being actively pursued.…”
Section: Discussionmentioning
confidence: 99%
“…In(OTf) 3 : indium(III) triflate; LiH: lithium hydride. [108] projected product (128) and its diastereomer (129), which had an indene substructure; these products were expected to have small biradical character according to DFT calculations. Singlecrystal analysis of 126 revealed that azulene and indene were fused on two sides of the molecular skeleton.…”
Section: Alkyne-based Cyclizationmentioning
confidence: 99%
“…Very recently, an elusive isomer of pyrene, bis-periazulene (138), was successfully synthesized by Yasuda et al (Scheme 21a). [108] The first attempt toward bis-periazulene can be dated back to 1955 by Reid, [33] and subsequent efforts were dedicated to this target. However, none of them were successful when conducting deprotonation of 137 + •ClO 4 − or two-electron oxidation of 2Li + •138 2− owing to the intrinsic instability of bis-periazulene.…”
Section: Alkyne-based Cyclizationmentioning
confidence: 99%
“…During the submission of our work, Yasuda et al. reported the synthesis of the triaryl derivatives of g , which exhibited singlet ground states, contrary to previous theoretical predictions for g [18b] . Therefore, the experimental access and the intrinsic properties of this kind of non‐alternative PHs remain elusive due to the lack of efficient synthetic strategy.…”
Section: Figurementioning
confidence: 77%